2020
DOI: 10.48550/arxiv.2004.02908
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microscopic Relaxation Channels in Materials for Superconducting Qubits

Abstract: Despite mounting evidence that materials imperfections are a major obstacle to practical applications of superconducting qubits, connections between microscopic material properties and qubit coherence are poorly understood. Here, we perform measurements of transmon qubit relaxation times T1 in parallel with spectroscopy and microscopy of the thin polycrystalline niobium films used in qubit fabrication. By comparing results for films deposited using three techniques, we reveal correlations between T1 and grain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
8

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 56 publications
0
12
0
8
Order By: Relevance
“…• пассивные элементы измерительной схемы, рассеивающие электрическую энергию в тепло. Для защиты от этих источников ИК-фотонов экраны, а в некоторых случаях и крышка держателя образца покрываются изнутри специальными поглощающими ИК-излу чение покрытиями [5][6][7][8][12][13][14], степень поглощения которых может достигать 0,95 в терагерцовом диапазоне электромагнитного излучения. В качестве поглощающих покрытий применяются промышленно выпускающиеся смолы [5][6][7][8][12][13][14][15] (например, Stycast 2850 FT, Marconi LAO, Eccosorb CR-series и др.)…”
Section: принципы экранирования защита от ик-излученияunclassified
See 2 more Smart Citations
“…• пассивные элементы измерительной схемы, рассеивающие электрическую энергию в тепло. Для защиты от этих источников ИК-фотонов экраны, а в некоторых случаях и крышка держателя образца покрываются изнутри специальными поглощающими ИК-излу чение покрытиями [5][6][7][8][12][13][14], степень поглощения которых может достигать 0,95 в терагерцовом диапазоне электромагнитного излучения. В качестве поглощающих покрытий применяются промышленно выпускающиеся смолы [5][6][7][8][12][13][14][15] (например, Stycast 2850 FT, Marconi LAO, Eccosorb CR-series и др.)…”
Section: принципы экранирования защита от ик-излученияunclassified
“…Для защиты от этих источников ИК-фотонов экраны, а в некоторых случаях и крышка держателя образца покрываются изнутри специальными поглощающими ИК-излу чение покрытиями [5][6][7][8][12][13][14], степень поглощения которых может достигать 0,95 в терагерцовом диапазоне электромагнитного излучения. В качестве поглощающих покрытий применяются промышленно выпускающиеся смолы [5][6][7][8][12][13][14][15] (например, Stycast 2850 FT, Marconi LAO, Eccosorb CR-series и др.) отдельно или в сочетании с дополнительными частицами на их поверхности (например, порошок SiC с разным размером частиц, уголь или графитовая пыль).…”
Section: принципы экранирования защита от ик-излученияunclassified
See 1 more Smart Citation
“…Superconducting qubits have traditionally been fabricated with either aluminum or niobium sputtered onto silicon or sapphire substrates. Niobium, in particular, generates multiple species of oxide on its surface with significant populations extending up to 10 nm into the metal [17], creating an unwanted environment for TLS to reside [18]. Alternative superconducting metals might exist that produce more uniform oxides or create cleaner interfaces between the metal and substrate.…”
Section: Introductionmentioning
confidence: 99%
“…In Nb-based superconducting qubits, atomic-scale characterisation with X-ray photoelectron spectroscopy and resonant inelastic X-ray scattering have found that a Nb-oxide layer readily forms at the interface [26][27][28] . Magnetic and charge defects in this Nb-oxide layer have been suggested as a significant source of dissipation 18,26,29 .…”
Section: Introductionmentioning
confidence: 99%